Molecular docking and molecular simulation studies for N-degron selectivity of chloroplastic ClpS from Chlamydomonas reinhardtii. (April 2023) - Wang, Ning; Gao, Jian-Guo; Wu, Ming-Wei
Abstract: Regarding the importance of N-degron pathway in protein degradation network, the adaptor protein ClpS recognizes the substrates bearing classical N-degrons, and delivers them to caseinolytic protease complex ClpAP for degradation. Interestingly, the majority of N-degrons located near the N-terminus of protein substrate are belonged to the hydrophobic type amino acids. Chloroplast, an important organelle for plant photosynthesis, contain a diversified Clp degradation system. Despite several studies have confirmed that chloroplastic ClpS is able to interact with classical N-degrons derived from prokaryotes, whereas, the molecular mechanism underlying how the chloroplastic ClpS protein could recognize the substrate tagged by N-degrons is still unclear until now. Chlamydomonas reinhardtii is a kind of unicellular model organism for photosynthesis researches, which possesses a large cup-shaped chloroplast, and the corresponding genome data indicates that it owns bacterial homologous adaptor protein, named CrClpS1. However, the relevant biochemical knowledges, and protein structure researches for CrClpS1 adaptor aren't reported up to date. The molecular interactions between CrClpS1 and possible N-degrons are undefined as well. Here, we build a reliable homology model of CrClpS1 and find a hydrophobic pocket for N-degron binding. We combine molecular docking, molecular dynamic simulations, and MM/PBSA, MM/GBSA binding free energy estimations to elucidate the molecular properties of CrClpS1-N-degron interactions. Besides, we investigate the conformational changes for CrClpS1-apo in water-solvent environment and analyze its possible biological significances through a long time molecular dynamic simulation. Specifically, the adaptor CrClpS1 displays the stronger interactions with Phe, Trp, Tyr, His and Ile with respect to other amino acids. Using the residue decomposition analysis, the interactions between CrClpS1 and N-degrons are heavily depended on several conservative residues, which are located around the hydrophobic pocket, implying that chloroplast isolated from Chlamydomonas reinhadtii adopts a relatively conservative N-degron recognition mode. Besides, the opening-closure of hydrophobic pocket of CrClpS1 might be beneficial for the N-degron selectivity. Graphical Abstract: ga1 Highlights: Chloroplastic CrClpS1 homology model of Chlamydomonas reinhardtii is developed and validated. Molecular docking of twenty amino acids towards CrClpS1 is performed to identify N-degron candidate. The opening-closure switching motion of hydrophobic pocket of CrClpS1 is observed by 2 µs molecular dynamic simulation. Obtaining the affinity ranking order of N-degrons by MM/PBSA. Identification of key residues within pocket through MM/GBSA and hydrogen bond analysis.